2007
DOI: 10.1111/j.1600-0854.2007.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐Terminal Prenylation of the CLN3 Membrane Glycoprotein Is Required for Efficient Endosomal Sorting to Lysosomes

Abstract: Mutations in the polytopic lysosomal membrane glycoprotein CLN3 result in a severe neurodegenerative disorder. Previous studies identified two cytosolic signal structures contributing to lysosomal targeting. We now examined the role of glycosylation and the C-terminal CAAX motif in lysosomal transport of CLN3 in nonneuronal and neuronal cells. Mutational analysis revealed that in COS7 cells, CLN3 is glycosylated at asparagine residues 71 and 85. Both partially and non-glycosylated CLN3 were transported correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 44 publications
1
58
0
Order By: Relevance
“…After incubation with primary and Alexa Fluor-coupled secondary antibodies and staining of nuclei with DAPI, coverslips were sealed in mounting medium (DAKO, Glostrup, Denmark). Double immunofluorescence microscopy was performed as described previously (22). Images were taken with a Leica digital scanning confocal microscope (Leica DMIRE2, 63ϫ magnification), and merge of images was performed using Adobe Photoshop software.…”
Section: Methodsmentioning
confidence: 99%
“…After incubation with primary and Alexa Fluor-coupled secondary antibodies and staining of nuclei with DAPI, coverslips were sealed in mounting medium (DAKO, Glostrup, Denmark). Double immunofluorescence microscopy was performed as described previously (22). Images were taken with a Leica digital scanning confocal microscope (Leica DMIRE2, 63ϫ magnification), and merge of images was performed using Adobe Photoshop software.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, this result suggests that the C-terminal cysteine residue(s) might be involved in controlling Btn1p activity, with the internalisation of Btn1p into the vacuole being a method of 'switching off' the protein. Studies on CLN3 had also shown that residues in the C-terminal tail were crucial for correct trafficking Modelling CLN3 mutations in S. pombe RESEARCH ARTICLE (Storch et al, 2004;Kyttala et al, 2005;Storch et al, 2007). In particular, inhibition of farnesylation of Cys435 causes more CLN3 to be located on the plasma membrane .…”
Section: Research Articlementioning
confidence: 99%
“…The C-terminus of CLN3 has a CAAX farnesylation site (Cys435), which is of importance because farnesylation is required for correct trafficking (Pullarkat and Morris, 1997;Storch et al, 2007). This cysteine residue is conserved (supplementary material Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human CLN3 has been located to chromosome 16p12 and encodes an integral membrane glycoprotein of 438 aminoacids (International Batten Disease Consortium, 1995). It possesses six transmembrane domains and the glycosilation varies in different tissues (Ezaki et al, 2003;Storch et al, 2007). Overexpressed CLN3 protein is localized in the lysosomes in non neuronal cells while it is detected in the endosomal/lysosomal structures and in the synaptosome in neurons (Kyttala et al, 2004;Luiro et al, 2001).…”
Section: Genementioning
confidence: 99%